Errores refractivos y su incidencia en los síntomas astenópicos en niños del sector 5 de junio Parroquia San Juan Cantón Puebloviejo, noviembre 2023-abril 2024. - Coello Cercado, Xiomara Nayeli (2024)
Sight is a fundamental element in the life of human beings because it contributes to their comprehensive development and adequate performance in different aspects of life; Despite this, it is affected by different factors, limiting vision by clearly preventing what is observed. Visual problems such as refractive errors (myopia, hyperopia, astigmatism) currently impact the general population and children, and another factor that influences the development of vision is asthenopic symptoms that in one way or another occur. are increasing due to refractive errors. Objective: Determine the incidence of refractive errors in asthenopic symptoms in children aged 10 to 12 years from the 5 de Junio sector, San Juan parish, Puebloviejo canton, November 2023-April 2024. Methodology: A basic, descriptive and cross-sectional research was used, as well as such as inductive and deductive methods. Likewise, survey and documentary review techniques (medical history) were applied, with their respective instruments aimed at a sample of 25 children. Results: 100% of parents state that their children suffer from some visual problem. Likewise, 60% of parents have not performed visual examinations on their infants and all infants have inadequate visual acuity. Conclusions: The main asthenopic symptoms that the children presented were: double or blurred vision, sensitivity to light, eye pain, redness and burning or itching. While, the most frequent refractive errors were: Hyperopia, Compound Hyperopic Astigmatism, Simple Hyperopic Astigmatism and Myopic Astigmatism.